A critical evaluation of methodological and mechanistic insights on probiotic-derived extracellular vesicles - Ronacher, Chantal; Gonzalez, Claudio F.; Lorca, Graciela L. (Frontiers in Nutrition, 2025)
Probiotic extracellular vesicles (pEVs) have emerged as promising postbiotics with potential applications in inflammatory diseases, infections, allergies, cancer treatment, autoimmune disorders, and even neurological and degenerative conditions. Yet despite the surge in research on pEVs, critical gaps and inconsistencies in study design, methodology, and mechanistic understanding hinder unlocking their full potential. This literature review provides a concise introduction to beneficial bacterial EVs, mechanistic insights into their role in interkingdom interactions, and current challenges in pEV research. We highlight methodological inconsistencies in model selection, control design, and effect measurement, discuss their consequences and provide recommendations to improve experimental rigor and comparability of results. These include methodological considerations like standardization strategies for pEV preparation, purification, formulation, and administration as well as general study design questions. Finally, we outline key avenues for future research, emphasizing the need for biomarkers to track pEV biodistribution, the identification of effector molecules, and a deeper understanding of their mechanistic targets, as well as their interactions with food components and their use as delivery systems, among others. By addressing these challenges, this review aims to provide a roadmap for advancing pEV research and facilitating their transition into clinical and biotechnological applications.